Pengenalan Internet of Things menggunakan Simulasi Cisco Packet Tracer untuk Siswa dan Mahasiswa di BPTI UHAMKA - Rizkiawan, M. Asep Rizkiawan; Kurniawan, Eko Kurniawan (Sinesia : Jurnal Pengabdian Masyarakat, 2024)
The Internet of Things (IoT) Basic Introduction Training using Cisco Packet Tracer was held at the UHAMKA Information Technology Development Agency (BPTI) with the aim of increasing the understanding of students and the general public about the basic concepts of IoT and its use through software simulations. IoT is a technology that is increasingly developing and plays an important role in various industrial sectors and daily life. However, limited access to IoT hardware is a challenge in the learning process. Therefore, simulation using Cisco Packet Tracer was chosen as a practical and effective solution. The method used in this training is action research with quantitative and qualitative approaches. The training involved a theory session on the basic concepts of IoT and a simulation practice session using Cisco Packet Tracer, in which participants created mini IoT projects such as a network simulation of a Smart Home System based on the Internet of Things. Evaluation was conducted through pre-test and post-test to measure the improvement of participants' understanding, as well as observation and interviews to obtain qualitative feedback. The results showed that the average pre-test score of the participants was 45.3, while the average post-test score increased significantly to 82.7. A total of 85% of participants successfully completed the IoT mini project, demonstrating their mastery of basic IoT concepts.